STUDYING, IMITATING BUYA HAMKA'S FIGURE AND PERSPECTIVE ON THE WORLD OF EDUCATION THROUGH THE THOUGHT OF HIS WRITINGS AND LITERATURE - Abdul Istiqlal; Afdhal Rinsik (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Current education is getting more challenges, one of which is that education takesplace in a setting made-up environment, since it should foster behavior which is useful for indivual ini the obtionfuture, not now. The purpose of this research is to find out what the concept of education world thought according to Buya HAMKA, so that it can be applied the contemporary world of education. This research used qualitative methods are used in this study, informan information, namely library research by collecting books written by HAMKA as primary data and other books that write about HAMKA as well written works in the form of journals, skrepstion,theses, and desertation to be studied and analysed to obtion conclution. In this research, the authors limit the studied and analyzed to obtain conclusion. I tfis stufy, the authors limit the research to only discussing and reviewing HAMKA’s concept of education word in Indonesia. Research shows that Buya Hamka’s concept of education world emphasizes maximum effort in personal growth and strengthening. From the result of this study, the authors structure the process of the emergence of Hamka’s thoughts, so that a common thread appears to be related to HAMKA education thoughts and their life jouney. Furthermore, the authot conducts analytical of study of HAMKA’s thoughts related to current conditions, so that the authors find the relevance of HAMKA world education thoughts to current conditions and in the end if this implemented it well be able to bring this nations to much better life.